1985
DOI: 10.1084/jem.161.5.1243
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 2 inhibits in vitro growth of human T cell lines carrying retrovirus.

Abstract: Human T cell leukemia virus (HTLV), which we previously called adult T cell leukemia virus (ATLV), is a possible causative agent of human adult T cell leukemia (ATL) (1). Since the HTLV genome was demonstrated not to contain a typical v-onc gene (2) and the HTLV proviral genome is integrated into random sites in cellular DNA of leukemia cells in each ATL patient (3), the mechanism of HTLV-induced oncogenesis is still unknown. The interleukin 2 (IL-2) autocrine hypothesis can be excluded as the mechanism of ATL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
1

Year Published

1986
1986
1991
1991

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…IL-2-stimulated phosphorylation of pp67 was similarly detected in IL-2-independent HTLV-I-transformed T-cell lines which express the high-and low-affinity receptors for IL-2. In contrast with IL-2-dependent cells, the growth of these cells is inhibited by the addition of IL-2 [39], and we have already proved that the growth-inhibitory signal is transduced from the high-affinity IL-2 receptors by analogy to the IL-2 growth signal [40]. MT-1 cells express only the low-affinity IL-2 receptors constitutively [37] and do not respond to IL-2 with regard to cell-growth promotion and inhibition [39].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…IL-2-stimulated phosphorylation of pp67 was similarly detected in IL-2-independent HTLV-I-transformed T-cell lines which express the high-and low-affinity receptors for IL-2. In contrast with IL-2-dependent cells, the growth of these cells is inhibited by the addition of IL-2 [39], and we have already proved that the growth-inhibitory signal is transduced from the high-affinity IL-2 receptors by analogy to the IL-2 growth signal [40]. MT-1 cells express only the low-affinity IL-2 receptors constitutively [37] and do not respond to IL-2 with regard to cell-growth promotion and inhibition [39].…”
Section: Discussionmentioning
confidence: 87%
“…In contrast with IL-2-dependent cells, the growth of these cells is inhibited by the addition of IL-2 [39], and we have already proved that the growth-inhibitory signal is transduced from the high-affinity IL-2 receptors by analogy to the IL-2 growth signal [40]. MT-1 cells express only the low-affinity IL-2 receptors constitutively [37] and do not respond to IL-2 with regard to cell-growth promotion and inhibition [39]. Interestingly the phosphorylation of pp67 (and pp63s) in MT-I was not enhanced by IL-2 at any dose (T. Ishii & K. Sugamura, unpublished work), so it is suggested that the pp67 phosphorylation signal may be transduced from the high-affinity IL-2 receptors.…”
Section: Discussionmentioning
confidence: 87%
“…Two classes of IL-2R differing in affinities to IL-2 were identified; these are high-and low-affinity receptors (11,16). The high-affinity receptor, but not the low-affinity receptor, is thought to mediate various functions such as internalization of IL-2 (4, 21), activation of protein kinase C (2), phosphorylation of certain cellular proteins (5,6), and enhancement of gene expression (1,12), and consequently to be involved in cell growth promotion (10) or inhibition in some cases (15) . two different chains, IL-2Rƒ¿ and ƒÀ chains, the IL-2Rƒ¿ chain corresponding to the Tac molecule detected by monoclonal antibody and the IL-2RƒÀ chain identified as 68-72kD glycoproteins (18,20 EffectsofWGA and H-47 Antibody after Additionof 1251-IL-2 We next examined the effects of lectins on IL-2R in the high-affinity state after addition of IL-2.…”
mentioning
confidence: 99%
“…The addition of purified IL-2 preparation did not alter the proliferative state of IL-2-independent ATL cells and cell lines (Tables 111 and IV). More recently, Sugamura et al (1985) observed that exogenous IL-2 added to the culture inhibited proliferation of 4 HTLV-I carrying T-cell lines derived from 3 HTLV-I healthy carriers and an ATL patient. In their discussion they suggested that those IL-2-dependent T-cell lines were possibly derived from activated normal T cells infected with HTLV-I in vivo, based on the observation that ATL leukemia cells can hardly proliferate in the presence of IL-2 during primary culture.…”
Section: Discussionmentioning
confidence: 99%